2018
DOI: 10.15421/011845
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of seedlings of native and alien species of the genus Bidens (Asteraceae) from different geographic populations to the action of heavy metals

Abstract: One approach to assessing the competitiveness of invasive species is a comparative analysis of the morphological, physiological, and reproductive traits of this species with native species of the same genus. The invasive species Bidens frondosa L. from the Asteraceae family, included in the list of the 50 most common and most aggressive invasive species in Europe, occupies the same ecological niche as the native species B. tripartita L., and displaces it from natural habitats. There is an obvious and growing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Both metals and salts have a toxic effect manifested in the reduction of the main root. The B. radiata species is more resistant to the effects of copper than other species of this class [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both metals and salts have a toxic effect manifested in the reduction of the main root. The B. radiata species is more resistant to the effects of copper than other species of this class [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that B. frondosa has higher seed mass and productivity, as well as dry mass and growth rates as compared to B. tripartita, and B. radiata in European Russia [9,18,19] and Western Europe [5]. Various authors have demonstrated the higher resistance of B. frondosa to heavy metals [13], as well as larger morphological variability under influence of environmental factors [17,22] in comparison to native Bidens congeners in the ecosystems of Eurasia.…”
Section: Introductionmentioning
confidence: 99%